Principal Leadership Innovation in Improving Teacher Performance in Integrated Islamic Schools - Luthfi Tegar Satrio Wibowo; Triono Ali Mustofa (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to reveal the innovative leadership strategies implemented by the principal of SMP IT Mutiara Insan Sukoharjo, to improve teacher performance. This study uses descriptive qualitative through direct observation, in-depth interviews, and documentary records. The research instruments are observation forms, interview questionnaires, and criteria for relevant documentation. The study's results indicate that these innovations improve teachers' motivation, competence, and job satisfaction. These leadership strategies align with Islamic teachings, create a harmonious work environment, and improve teacher performance. This study concludes that teacher-centered leadership innovations and learning are the keys to improving the quality of education in Islamic schools.